PENGAJIAN MAJLIS TA’LIM NURUL KARIMAH DAN PENGARUHNYA TERHADAP PERILAKU RELIGIUSITAS JAMA’AH - Miftakhul Djannah; Khoirin Niswati; Muhtadi; Adibah Jauhari (FAI- Undar, 2020)
This study aims to determine the religious values applied by the congregation and the form of implementation of these values in daily life. This thesis seeks to measure the level of the results of the study of the interpretation of the Qur'an in the lives of the Nurul Karimah congregation. This thesis is a field study object with descriptive research that presents data through interviews, observation and documentation. This research step begins by collecting data on congregational behavior and recitation materials. The primary data of this thesis was obtained directly from the original source, namely individuals or the community through research and interviews. The secondary data in the form of data sources derived from previous research, such as journals, books, and other references.The results of this study are as follows: first, the study of interpretation in the village of Gagakan has begun to reverberate for 3 years by Siti Badriyah in 1992 with members of the Nurul Karimah congregation. This study forms religious values as a result of teaching for the life of the congregation. The materials and methods of recitation which include prayer in QS. al-Ankabut: 45, Fadhilah Basmalah, Hamdalah and its fadhilah, and Shalawat and its fadhilah which are packaged with lecture and weton methods. Through these materials and methods, religious values are formed, including: prayer in congregation, harmony in household life and neighbors, mutual respect, patience and istiqmah, qanaah. Second, the study of this interpretation implicitly has a great influence on the lives of the congregation. Consciously, they suggest themselves to be better after the recitation takes place and practice it. The implementation of this value is in the form of congregational morals, the urgency of the study of interpretation, and things that are influential. As for the urgency of the recitation, which is expected to guide their lives for the better, observations have received a positive response and have been successfully practiced by the congregation in themselves and their respective families. Third, the implementation of religious values produced in the study of interpretations on a regular basis, makes the lives of the congregation more organized. Based on social experience, the respondents can carry out reading yasin, tahlil, asthma al-husna, praying, aurad-aurad, and guarding themselves from Allah's prohibition. The social experience and behavior of the respondent is a positive form of recitation of the interpretation of the Qur'an.